Emmanuel's dream : the true story of Emmanuel Ofosu Yeboah - Thompson, Laurie Ann (Schwartz & Wade Books, 2015)
Born in Ghana, West Africa, with one deformed leg, he was dismissed by most people--but not by his mother, who taught him to reach for his dreams. As a boy, Emmanuel hopped to school more than two miles each way, learned to play soccer, left home at age thirteen to provide for his family, and, eventually, became a cyclist. He rode an astonishing four hundred miles across Ghana in 2001, spreading his powerful message: disability is not inability. Today, Emmanuel continues to work on behalf of the disabled.